The trend in deaths from alcoholic liver disease (ALD) over the past decade - Gopika Biju Pillai; Vedamurthy Adhiyaman; Peter Hobson (Clinical Medicine)
Introduction: Deaths from alcoholic liver disease (ALD) in England and Wales are increasing. Despite persistent multifaceted government policies aimed at reducing alcohol consumption, their impact does not appear to be as effective as expected. Even though there is a male preponderance, deaths from ALD are rapidly increasing in women. The aim of this study was to look at the trend in the number of deaths resulting from ALD and the differences between men and women. Methods: We extracted data on all deaths resulting from ALD from the Office of the National Statistics using the ICD code K.70 for England and Wales over the last 10 years (2013- 2023).1 We compared the difference in trend between men and women. Results: There was a steady increase in the total number of deaths resulting from ALD over the past decade. It increased from 4,524 in 2013 to 6,869 in 2023 (52% increase). For men, deaths resulting from ALD rose from 3,000 to 4,504 and, in women, from 1,524 to 2,365 over the same period. This corresponds to a 50% increase in men and 55% increase in women. Discussion: Despite public health warnings, the number of deaths resulting from ALD has been steadily increasing in both men and women over the past decade. Although the total number of deaths was less in women compared with men, the percentage increase in women was significantly higher compared with men. Evidence suggests that many of the effects of alcohol pose a greater risk to women's physical health at lower consumption levels compared with men. There is also evidence of alcohol marketing targeting women, perpetuating gendered stereotypes. We should continue to be proactive in public health interventions and gender specific interventions to reduce deaths resulting from ALD in both sexes.